Characterization of electrostatically defined bottom-heated InAs nanowire quantum dot systems - Sven Dorsch; Sofia Fahlvik; Adam Burke (New Journal of Physics, 2021)
Conversion of temperature gradients to charge currents in quantum dot systems enables probing various concepts from highly efficient energy harvesting and fundamental thermodynamics to spectroscopic possibilities complementary to conventional bias device characterization. In this work, we present a proof-of-concept study of a device architecture where bottom-gates are capacitively coupled to an InAs nanowire and double function as local joule heaters. The device design combines the ability to heat locally at different locations on the device with the electrostatic definition of various quantum dot and barrier configurations. We demonstrate the versatility of this combined gating- and heating approach by studying, as a function of the heater location and bias, the Seebeck effect across the barrier-free nanowire, fit thermocurrents through quantum dots for thermometry and detect the phonon energy using a serial double quantum dot. The results indicate symmetric heating effects when the device is heated with different gates and we present detection schemes for the electronic and phononic heat transfer contribution across the nanowire. Based on this proof-of-principle work, we propose a variety of future experiments.